Isatuximab for the treatment of multiple myeloma: current clinical advances and future directions - Richardson, Paul G.; O’Donnell, Elisabeth K.; O’Gorman, Peter; Leypoldt, Lisa B.; Laubach, Jacob; Gay, Francesca; Leleu, Xavier; Facon, Thierry; Moreau, Philippe; Dimopoulos, Meletios A.; Goldschmidt, Hartmut; Mai, Elias K.; et al. (Expert opinion on investigational drugs, 2025)
The addition of the anti-CD38 monoclonal antibody isatuximab to standard therapies is transforming the care of patients with newly diagnosed multiple myeloma (NDMM), as previously seen in the relapsed/refractory setting. This is particularly important for patients with NDMM as early treatment with effective, well tolerated therapies may ensure better clinical outcomes. Here, we examine recent results from pivotal Phase 3 and 2 clinical trials that demonstrate efficacy and safety of isatuximab across multiple combinations, for both transplant-ineligible and transplant-eligible NDMM patients. We then evaluate long-term outcomes from the IKEMA and ICARIA-MM trials as well as real-world evidence emerging from analyses conducted in patients with relapsed/refractory MM (RRMM). Further, we address current approaches to optimize treatment with isatuximab-based combinations involving changes in bortezomib or dexamethasone dosing. Lastly, we review current findings with new administration modalities developed to optimize delivery of isatuximab in the clinic. Supported by multiple lines of high-level evidence, isatuximab in combination with standard-of-care backbone therapies produces triplet or quadruplet regimens with enhanced efficacy and consistent safety for the treatment of patients with NDMM and RRMM.